Maqashid Syari’ah Menjawab Tantangan Post-Truth Era: Urgensi Hifẓ Al-‘Aql Sebagai Penyaring Informasi - Al Wasim, Arif (International Journal Ihya' 'Ulum al-Din, 2019)
The development of information technology has an impact on the spread of false news, false data, and hate speech, which is difficult to control. Truth mixed with badness will be ambiguous and biased. This is the most visible symptom or symptom of the post-truth era. In this context, the concept of hifáº“ al-â€˜aql in the maqÄá¹£id syarÄ«'ah can be used as a solution to deal with the negative symptoms above. This research is focused on how far the concept of hifáº“ al-qaql can be used as an information filter. The data's research is library research. The data collection method uses the documentation method, which is: collecting, then analyzing the data collected. After that, data analysis is carried out by means of data reduction, presentation of data in narrative form, and concluding. This study concludes that the concept of hifáº“ al-â€˜aql can be extended to mental and intellectual functions. The meaning of hifáº“ al-â€˜aql is expanded by making reason as a guide, and controller for rationality (â€˜aqlaniyah). This expansion of meaning emphasizes that filtering information before it is conveyed to others is a must, and worthy of worship. Vice versa, the spread of news and hate speech received without verification is an action that is contrary to the principle of hifáº“ al-qaql, prohibited acts, and has syar'i consequences.Â